GROWTH OF TiO2 THIN FILMS USING MOCVD FOR HYDROGEN GAS SENSING APPLICATION - ARIEF MUSTAJAB ENHA MARYONO (NIM: 20215015), MUHAMMAD
Hydrogen has potential as alternative and clean energy storage medium for reducing use of fossil fuel. With fuel cell technology, hydrogen can be used as fuel for transportation or electricity generation. However, in realizing hydrogen as future fuel still facing some obstacles from the public perception of safety in using hydrogen in daily life. Hydrogen known as one of the combustible and explosive gas in range of 4 % - 75 % mixture with air. A device which can detect low concentration of hydrogen in air is needed to ensure the safety of hydrogen use in the future. Hydrogen gas sensor become one of the solution of safety concern. One of the most investigated hydrogen sensor type is sensor based on semiconducting metal oxide (MOX). Thin kind of hydrogen sensor able to measure low hydrogen concentration in atmospheric condition and also has simple device structure. One of the development of MOX hydrogen sensor relied on the MOX materials as sensor element. One of the investigated MOX materials is TiO2 which has good thermal and chemical stability, but poor sensitivity over hydrogen gas. In this research, TiO2 thin films will be grown using MOCVD to make hydrogen gas sensor device. TiO2 thin film properties are attributed to growth parameter and hydrogen gas sensor performance parameters also are attributed to thin films properties. TiO2 thin films are grown using MOCVD method on Si(100) as substrate and TTIP as a precursor. Growth parameters are varied in substrate temperature from 300 oC to 500 oC. Thin film properties were characterized using XRD, SEM, and EDS to identify crystal phase and orientation, surface morphology and cross section, also atomic composition of the TiO2 thin films. Thin film grown at 300 oC has anatase crystal with dominated orientation at (213), growth with 71 nm thickness, non-uniform grain size between 20 – 40 nm, and good stoichiometry (atomic ratio of Ti and O is 1 : 2). Thin films grown at 400 oC and 500 oC has mixed crystal phase of anatase and rutile, relatively uniform and larger grain size between 30 – 40 nm, growth with thickness of 103 nm and 381 nm, and observed oxygen vacancies because of Ti3+ ions are formed in TiO2 thin films. Substrate temperature can affect the properties of TiO2 thin films including crystal phase and orientation, grainsize, film thickness, and also atomic composition (stoichiometry), Hydrogen gas sensors were fabricated by depositing interdigitated electrode on TiO2 thin films. The Au/Pt electrode is deposited using thermal evaporation method and interdigit patterns were made using ion beam lithography. Hydrogen gas sensors were labelled as sensor A, B, and C for thin films with growth temperature of 300 oC, 400 oC, and 500 oC. Hydrogen gas sensors were tested on different operational temperature from room temperature to 150 oC and also in different concentration of H2 gas from 1.000 ppm to 10.000 ppm. The measurement result of hydrogen gas sensor performances was interpreted and analyzed including dynamic response, metrological parameters, and static characteristic of gas sensor attributed to properties of TiO2 thin films as sensor element. As operating temperature increase the response of three sensor also increase up to certain value then decreasing. This temperature dependence of response show that gas sensors has optimal operating temperature. Sensor A has the highest response compared to other two sensors with 24,33 % of response at 100 oC operating temperature and has 91 s response time and 99 s recovery time. The response and recovery time decrease with increasing temperature producing faster response and recovery of sensors. Transient response of sensor A has shown the different magnitude of response to different gas concentration. The response show to the half power relation to the gas concentration. This function show there is saturation value of hydrogen gas sensor response to higher hydrogen concentration which is unfavorable for sensor. Hydrogen gas sensor with TiO2 thin films growth using MOCVD was able to detect hydrogen gas concentration. The best response from hydrogen gas sensor is 32,15 % at 100 oC operating temperature, which is still lower than commercial gas sensor. The TiO2 thin films with smaller grain size and ordered orientation crystal gives higher response to hydrogen gas.